2005
DOI: 10.1007/s00421-005-1349-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body heating slows carotid baroreflex response in human subjects

Abstract: Heat stress increases sympathetic activity and decreases parasympathetic activity to the heart. To test the hypothesis that carotid baroreflex responses of heart rate (HR) and systemic blood pressure become slowed with altered autonomic nerve activities during whole-body heat stress, we determined changes in HR and mean arterial pressure (MAP) in response to approximately 5 s of 40 mmHg neck pressure (NP) and of -65 mmHg neck suction (NS) in normothermia and during whole-body heating produced by a hot water-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Overall, our findings suggest that older individuals exhibit sluggish cardiovascular responses to simulated carotid hypertension, which may be due, in part, to age-related reductions in resting cardiac parasympathetic tone. Previous work in young subjects has observed delayed carotid-cardiac responses during heat stress (Yamazaki & Sone, 2005) and dynamic exercise (Strange et al 1990;Linnarsson et al 1996;Sundblad & Linnarsson, 1996). These studies suggested that such delays were attributable to the reductions in cardiac parasympathetic nerve activity (Keyl et al 2001) and/or the increases in SNA (Yang et al 1994;Sundblad & Linnarsson, 1996) that are typically elicited by these stimuli (Robinson et al 1966;Mitchell, 1990;Kenney et al 1995;Niimi et al 1997).…”
Section: Time and Frequency Domain Indices Of Heart Rate Variabilitmentioning
confidence: 95%
See 2 more Smart Citations
“…Overall, our findings suggest that older individuals exhibit sluggish cardiovascular responses to simulated carotid hypertension, which may be due, in part, to age-related reductions in resting cardiac parasympathetic tone. Previous work in young subjects has observed delayed carotid-cardiac responses during heat stress (Yamazaki & Sone, 2005) and dynamic exercise (Strange et al 1990;Linnarsson et al 1996;Sundblad & Linnarsson, 1996). These studies suggested that such delays were attributable to the reductions in cardiac parasympathetic nerve activity (Keyl et al 2001) and/or the increases in SNA (Yang et al 1994;Sundblad & Linnarsson, 1996) that are typically elicited by these stimuli (Robinson et al 1966;Mitchell, 1990;Kenney et al 1995;Niimi et al 1997).…”
Section: Time and Frequency Domain Indices Of Heart Rate Variabilitmentioning
confidence: 95%
“…In young healthy individuals, a delay in the latency of the peak cardiac baroreflex response has been reported during both heat stress (Yamazaki & Sone, 2005) and dynamic exercise (Strange et al 1990; Linnarsson et al 1996; Sundblad & Linnarsson, 1996). Although not directly tested in these studies, it was suggested that the mechanism for this prolonged response is the increase in cardiac sympathetic tone (Yang et al 1994; Sundblad & Linnarsson, 1996) and/or reduction in cardiac parasympathetic tone (Keyl et al 2001) that are elicited by these stimuli (Robinson et al 1966; Mitchell, 1990; Kenney et al 1995; Niimi et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water immersion is commonly used for rehabilitation, 1 therapeutic purposes, 22 passive induction or prevention of hyperthermic 20,23 or hypothermic stress, 21 and more recently as a mode of recovery from exercise. 24 The anomalous properties of water may improve 3 or reduce subsequent muscle functioning, 19 depending upon immersion techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The rise suggests that the capacity for a tachycardiac response to the rapid onset of hypotension is reduced and the capacity for a bradycardiac response to sudden hypertension is increased. To address whether the reduced responsiveness of HR to rapid hypotensive stimulation is due to a slowing of the response, Yamazaki et al 60) examined the effect of whole-body heating on the response time of HR and blood pressure following 5 s of neck pressure (NP) at 40 mmHg during supine rest. Whole-body heating increased significantly from the onset of NP until the peak of the tachycardiac response (3.93±0.35 s in normothermia and 5.20±0.24 s during heating), and from the onset of NP until the peak of the blood pressure response (6.75±0.51 s in normothermia and 9.39±0.62 s during heating).…”
Section: ) Effect Of Heat Stress On Baroreflex Control Of Peripheralmentioning
confidence: 99%